2002
DOI: 10.1001/archpedi.156.9.863
|View full text |Cite
|
Sign up to set email alerts
|

Lead Poisoning and Asthma

Abstract: There was no increased likelihood of asthma diagnosis or symptoms among young children with lead poisoning. Children with lead poisoning also had delayed medical care. These data may help guide interventions aimed at preventing or reducing the impact of lead poisoning and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These findings are also supported by the results of a previous study showing higher prevalence of respiratory symptoms for phlegm, shortness of breath and diagnosed asthma in industrial workers exposed with lead (6). However, there was no increased likelihood of asthma diagnosis or symptoms among young children with lead poisoning (26). The possible reason for this discrepancy is perhaps the long period of lead exposure in studied workers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are also supported by the results of a previous study showing higher prevalence of respiratory symptoms for phlegm, shortness of breath and diagnosed asthma in industrial workers exposed with lead (6). However, there was no increased likelihood of asthma diagnosis or symptoms among young children with lead poisoning (26). The possible reason for this discrepancy is perhaps the long period of lead exposure in studied workers in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…One study in Poland found blood lead levels to be inversely associated with FVC in children aged 10–15 years old (Little et al 2017). A study using Missouri Medicaid claims data showed no relationship between diagnosed asthma and elevated lead levels (Rabito et al 2013), nor was there a relationship between elevated lead levels and diagnosed asthma among children seen at a Chicago inner-city health center (Myers et al 2002). In contrast, among 930 kindergarten students in Taiwan, lead levels ≥ 5μg/dL were positively associated with asthma (odds ratio=5.5, 95% CI: 1.7 to 17.9) (Wang et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Short-term PM exposure had indicated Statistical modeling complex health data increased risk of morbidity (hospitalizations and emergency visits) with (lag period 2-3 days) and also increased risk of mortality due to respiratory conditions [13,17,[20][21][22][23][24][25]. Ambient Pb exposure and its association with asthma morbidity, among humans, were not extensively studied except in cases, where lead poisoning related asthma attacks among children in which significant effect was justified [26]. A review article showed that the mechanism that connects lead exposure to asthma was through oxidative stress and immune and inflammatory response alternations [27].…”
Section: Introductionmentioning
confidence: 99%